Pengaruh Kualitas Layanan, Citra Merek, dan Diferensiasi Produk terhadap Keputusan Pembelian pada Cafe 67 Kecamatan Kencong Kabupaten Jember - Muhammad Khaberun Al Faruq; Seno Sumowo; Nursaidah Nursaidah (BUDGETING : Journal of Business, Management and Accounting, 2022)
The purpose of this study is to understand the influence of service quality, brand image, and product differentiation on purchasing decisions at Cafe 67 Kencong District, Jember Regency. The population in this study were visitors to Cafe 67 who made purchases at Cafe 67 Kencong in Jember Regency. The purposive sampling method is carried out with the step of disseminating questions through a questionnaire to visitors to find out the answers that have been filled out. The total population of this study is large and unlimited. Therefore, the sample to be studied amounted to 100 respondents. This study uses primary data and multiple linear regression analysis as an analytical tool that aims to understand the influence of free variables on bound variables. The results of the study from multiple linear regression tests showed that service quality, brand image, and product differentiation showed a significant positive influence on purchasing decisions. From the results of the study, it can be concluded that good service quality, a quality brand image, and high product differentiation will improve the purchasing decision of Cafe 67 Kencong, Jember Regency. Keywords: Brand Image, Product Differentiation, Service quality and Purchase Decision.